Analysis of β-Catenin Signalling Activity Suggests Differential Regulation of Ontogenetically Distinct Dentate Granule Neuron Populations - Billmann, Charlotte; Schäffner, Iris; Heppt, Jana; Lie, Dieter Chichung (International Journal of Developmental Neuroscience, 2025)
In mammals, the dentate gyrus of the hippocampus is one of the few regions where neurogenesis continues throughout life. As a result, the dentate gyrus harbours neurons of ontogenetically different origin. Notably, ontogenetically different dentate granule neurons (DGNs) are morphologically distinct and fulfil specialized functions in hippocampal information processing and plasticity. Development of adult-born DGNs is tightly controlled by signals released by the complex cellular environment of the adult dentate gyrus. In mice, an adult-like cytoarchitecture of the dentate gyrus is observed only after postnatal Week 2. The question therefore arises when the signalling environment controlling adult neurogenesis is established and whether development of ontogenetically distinct DGNs is subject to the same regulatory pathways. Here, we analyse BATGAL reporter mice to determine the temporal development of β-catenin-signalling activity in the murine DGN lineage. We show that the β-catenin-signalling pattern, which is essential for precise dendritogenesis and neuronal maturation in adulthood, emerges only around 2 weeks after birth and continues to be refined over the next weeks. These results indicate that the signalling environment controlling adult neurogenesis is only gradually established and suggest that the development of ontogenetically distinct DGNs is controlled by different mechanisms.
CRIS-Team Scopus Importer:2025-02-28
Keywords: dentate gyrus; neurogenesis; niche; β-catenin signalling

Phosphorylation Modulates the Subcellular Localization of SOX11 - Balta, Elli-Anna; Wittmann, Marie-Theres; Jung, Matthias; Sock, Elisabeth; Häberle, Benjamin; Heim, Birgit; Von Zweydorf, Felix; Heppt, Jana; von Wittgenstein, Julia; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Frontiers in Molecular Neuroscience, 2018)
SOX11 is a key Transcription Factor (TF) in the regulation of embryonic and adult neurogenesis, whose mutation has recently been linked to an intellectual disability syndrome in humans. SOX11's transient activity during neurogenesis is critical to ensure the precise execution of the neurogenic program. Here, we report that SOX11 displays differential subcellular localizations during the course of neurogenesis. Western-Blot analysis of embryonic mouse brain lysates indicated that SOX11 is post-translationally modified by phosphorylation. Using Mass Spectrometry, we found 10 serine residues in the SOX11 protein that are putatively phosphorylated. Systematic analysis of phospho-mutant SOX11 resulted in the identification of the S30 residue, whose phosphorylation promotes nuclear over cytoplasmic localization of SOX11. Collectively, these findings uncover phosphorylation as a novel layer of regulation of the intellectual disability gene Sox11.
EVALuna2:35742

β-catenin signaling modulates the tempo of dendritic growth of adult-born hippocampal neurons - Heppt, Jana; Wittmann, Marie-Theres; Schäffner, Iris; Billmann, Charlotte; Zhang, Jingzhong; Vogt-Weisenhorn, Daniela; Prakash, Nilima; Wurst, Wolfgang; Taketo, Makoto Mark; Lie, Dieter Chichung (EMBO Journal, 2020)
In adult hippocampal neurogenesis, stem/progenitor cells generate dentate granule neurons that contribute to hippocampal plasticity. The establishment of a morphologically defined dendritic arbor is central to the functional integration of adult-born neurons. We investigated the role of canonical Wnt/β-catenin signaling in dendritogenesis of adult-born neurons. We show that canonical Wnt signaling follows a biphasic pattern, with high activity in stem/progenitor cells, attenuation in immature neurons, and reactivation during maturation, and demonstrate that this activity pattern is required for proper dendrite development. Increasing β-catenin signaling in maturing neurons of young adult mice transiently accelerated dendritic growth, but eventually produced dendritic defects and excessive spine numbers. In middle-aged mice, in which protracted dendrite and spine development were paralleled by lower canonical Wnt signaling activity, enhancement of β-catenin signaling restored dendritic growth and spine formation to levels observed in young adult animals. Our data indicate that precise timing and strength of β-catenin signaling are essential for the correct functional integration of adult-born neurons and suggest Wnt/β-catenin signaling as a pathway to ameliorate deficits in adult neurogenesis during aging.
CRIS-Team Scopus Importer:2020-09-25
Keywords: adult neurogenesis; aging; dendrite; hippocampus; Wnt signaling